Hubungan Lingkar Lengan Atas dan Indeks Massa Tubuh terhadap Risiko Anemia pada Wanita Usia Subur di Tanjung Batu - Samirah, Thaliah; Yuliarti, Yuliarti (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2025)
Anemia in women of reproductive age (WRA) is a global health issue closely related to nutritional status. Upper Arm Circumference (UAC) and Body Mass Index (BMI) are common indicators used to assess an individual's nutritional status. The risk of anemia in WRA can impact reproductive health, increasing the risk of infertility, pregnancy complications, fetal growth retardation, and the birth of low birth weight (LBW) babies. This study aims to analyze the relationship between UAC and BMI with the risk of anemia in WRA. A descriptive analytical method with a quantitative approach using a cross-sectional study design was employed. The sample consisted of 88 WRA selected through purposive sampling. UAC was measured using a UAC tape, BMI was calculated from anthropometric measurements, and hemoglobin levels were measured using Easy Touch Hb. Data were analyzed using the chi-square statistical test to examine the relationships between variables. The results showed that 2.3% of WRA had anemia, 11.4% had chronic energy deficiency (CED), 17% had undernutrition, and 14.8% had overnutrition. Bivariate analysis showed no significant relationship between UAC and BMI with the risk of anemia in WRA in the working area of the Tanjung Batu Health Center, Ogan Ilir District. Nevertheless, monitoring nutritional status through UAC and BMI can be an important strategy in preventing anemia in WRA, particularly in pregnancy preparation. Therefore, nutrition education programs and iron supplementation should be intensified.